2008
DOI: 10.1507/endocrj.k07e-083
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Thyroid Function and Heart Valve Sclerosis. Results from a Population-Based Study

Abstract: Abstract. Objectives: Thyroid dysfunction is associated with detrimental cardiovascular effects. We analyzed whether thyroid status is associated with aortic valve sclerosis (AVS) and mitral annular calcification (MAC) as markers of generalized atherosclerosis. Design: Data of 2065 subjects (923 women and 1142 men) aged ≥45 years from the Study of Health in Pomerania (SHIP) were analyzed with respect to low, medium and high TSH levels. Logistic regression models were adjusted for major confounders of atheroscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
2
2
0
Order By: Relevance
“…However, so far no studies investigated whether and to which extent measurements of aortic and carotid wall thickness are correlated. Furthermore, the results of our study are in agreement with several other population-based studies which reported associations between high TSH and markers closely related to atherosclerosis such as endothelial dysfunction [32], heart valve sclerosis [33], retinal arteriolar narrowing [34] and oxidized low-density lipoprotein [35]. Hence, there is some evidence that serum TSH levels are positively associated with atherosclerosis, which is further supported by the results of our study.…”
Section: Discussionsupporting
confidence: 93%
“…However, so far no studies investigated whether and to which extent measurements of aortic and carotid wall thickness are correlated. Furthermore, the results of our study are in agreement with several other population-based studies which reported associations between high TSH and markers closely related to atherosclerosis such as endothelial dysfunction [32], heart valve sclerosis [33], retinal arteriolar narrowing [34] and oxidized low-density lipoprotein [35]. Hence, there is some evidence that serum TSH levels are positively associated with atherosclerosis, which is further supported by the results of our study.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with previous studies showing associations between low fT4 levels and elevated levels of inflammatory markers [17], mitral annular calcification [24], and thickening of the carotid intima media [1821] in stroke patients with euthyroidism. Since our findings were obtained with a relatively large and inclusive sample of ischemic stroke patients, we strengthen the case for targeted screening of ischemic stroke patients with low-normal thyroid function for carotid atheromatous plaques.…”
Section: Discussionsupporting
confidence: 93%
“…In the general population, hypothyroidism is associated with increased serum osteoprotegerin levels, an inhibitor of vascular calcification in experimental studies but a marker of vascular calcification, atherosclerosis and cardiovascular events in clinical studies, which may normalize with exogenous thyroid hormone treatment [122][123][124][125][126]. Elevated TSH and low FT4 have been associated with valvular and coronary artery calcification [127,128].…”
Section: Vascular Calcificationmentioning
confidence: 99%